Cadmium in the North Atlantic: Implication for global cadmium–phosphorus relationship. (June 2015) - Wu, Jingfeng; Roshan, Saeed
Abstract: Dissolved cadmium (Cd) distribution was determined in the tropical–subtropical North Atlantic along GEOTRACES GA03 section (US GEOTRACES 2010 and 2011 cruises). A pronounced mid-depth Cd maximum extends from the productive tropical eastern North Atlantic where subsurface waters in the upper themocline are depleted in dissolved oxygen. At this Cd maximum, Cd depletion relative to phosphate (PO4) is observed in the Cd vs. PO4 plot, but the relative Cd depletion is not present in the plot of Cd:PO4 ratio vs depth. The apparent relative Cd depletion at the Cd maximum appears to reflect a depth-dependent variation of Cd:PO4 ratio commonly observed in the world ocean. Such depth dependent variation of Cd:PO4 ratio may result from the regeneration of Cd from Cd-poor particulate organic carbon (POC) in the upper ocean and from Cd-rich POC in the deep ocean. The vertical Cd regeneration may lead to the observed difference in deep water Cd:PO4 ratio between the North Atlantic and North Pacific, if Cd to phosphorus ratio in the POC flux to the deep ocean is higher in the Pacific than in the Atlantic.